2003
DOI: 10.1097/00124784-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Media Campaign Influences Parentsʼ Opinions about Their Children and Tobacco

Abstract: Though parents who smoked in high school and those who did not agreed that children are targeted and should be banned from tobacco use, parents who did not smoke in high school believed it more strongly. Parents who had a history of smoking changed more on the issue of banning, perhaps because they had more room to change. The study concluded that media campaigns can change parents' attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Descriptive research has assessed attitudes towards tobacco industry regulation in diverse samples including: adults in Ontario;54 Mississippi parents before and after a youth-targeted, counter-industry state media campaign;62 Korean immigrant, male smokers;63 school nurses64 and New Zealand politicians 65. In a sample of smokers in four countries, thinking about the conduct of tobacco companies and belief that the industry should take more responsibility for tobacco's harms were independently predictive of support for industry regulation,46 and counter-industry beliefs were associated with noticing anti-smoking information, tobacco ads and secondhand smoke restrictions 8…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive research has assessed attitudes towards tobacco industry regulation in diverse samples including: adults in Ontario;54 Mississippi parents before and after a youth-targeted, counter-industry state media campaign;62 Korean immigrant, male smokers;63 school nurses64 and New Zealand politicians 65. In a sample of smokers in four countries, thinking about the conduct of tobacco companies and belief that the industry should take more responsibility for tobacco's harms were independently predictive of support for industry regulation,46 and counter-industry beliefs were associated with noticing anti-smoking information, tobacco ads and secondhand smoke restrictions 8…”
Section: Resultsmentioning
confidence: 99%
“…These school nurses had moderately negative attitudes toward tobacco companies. In contrast, in a 1999 telephone survey of voters in Mississippi, most respondents held weakly negative attitudes toward tobacco companies (Carver et al, 2003). Attitudes toward tobacco companies may have deteriorated in these 5 years, or school nurses may be more negative toward tobacco companies than the general voting public listed in the phone directory.…”
Section: Discussionmentioning
confidence: 91%
“…The Tobacco Company Attitudes subscale consisted of 11 questions (e.g., "Tobacco companies are to blame for youth smoking") about tobacco companies being blameworthy for youth smoking (2 items), focused on youth (6 items), and similar to other companies (3 items, reverse scored), slightly adapted from Sly, Hopkins, Trapido, and Ray (2001) and Carver, Reinert, Range, and Campbell (2003). They were scored on a 5-point scale ranging from 1 (strongly agree) to 5 (strongly disagree) so that low numbers indicated more agreement with the perception that tobacco companies do bad things.…”
Section: Methodsmentioning
confidence: 99%
“…A US study also showed that TV advertisements are the most frequently mentioned source of help among recent quitters of smoking [28]. Furthermore, a number of studies have shown that mass media campaigns enhance improvements in attitude toward healthy behavior, such as better diet, exercise, illegal drug prevention, safe sex, and smoking cessation [29][30][31][32][33][34][35][36]. The World Health Organization (WHO) reports on developing countries also support mass media interventions to increase the knowledge of HIV transmission and boost awareness of health providers [37].…”
Section: Discussionmentioning
confidence: 99%